A cross-sectional survey on sleep quality, mental health, and academic performance among medical students in Saudi Arabia - Abdullah Murhaf Al-Khani; Muhammad Ishaque Sarhandi; Mohamed Saddik Zaghloul; Mohammed Ewid; Nazmus Saquib (BMC Research Notes, 2019)
Abstract Objective Adequate sleep is integral to better mental health and facilitates students’ learning. We aimed to assess sleep quality among medical students and to see whether it was associated with their mental health (e.g., depression, anxiety, and stress) and academic performance. Results A total of 206 responded, and 95 of them had complete data on demography, lifestyle, academic performance, sleep quality (Pittsburgh Sleep Quality Index), and mental health (Depression Anxiety Stress Scales). The prevalence of poor sleep was 63.2%; it was higher among students who were physically inactive and had more screen time. Poor sleepers demonstrated higher academic performance than sufficient sleepers (p = 0.04). The prevalence of depression, anxiety, and stress were 42%, 53%, and 31% respectively. Sleep quality was significantly associated with depression (p = 0. 03), anxiety (p = 0.007), and stress (p = 0.01).